Foundations of library and information science - Rubin, Richard (Neal-Schuman Publishers, 2010)
This book includes a completely fresh discussion of the most current issues and key technological developments in the field. Rubin explores the ever-growing impact of the World Wide Web, the impact of blogs, wikis, and social networks on services, electronic publication including e-books, digital libraries, digital preservation, mass digitization, and digital repositories, and Functional Requirements for Bibliographic Records